PENGARUH BAURAN ECERAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA MINIMARKET DI KOTA BOGOR - Faisal Luthfi Anshori; Titiek Tjahja Andari (Fakultas Ekonomi Universitas Djuanda, 2016)
The aims of this research is to determine the effect Retailing Mix consist of product, price, promotion, service, ambience of the store, the location of consumer buying decisions in Bogor city’s minimarket both simultantly and partially. Samples are taken from 100 respondents using the random sampling method. Data are collected by questionnaires. Instrument tests are using validity, reliability, and classical assumption method while the data analysis is using multiple regression analysis, correllation analysis, coefition of determination analysis and statistical test (F test and t test). The results show that the X variable of retailing mix consist of product (X1), price (X2), promotion (X3), services (X4), the ambience of the store (X5), location (X6) are valid and reliable. It has significant effect on the consumer’s buying in the minimarket at Bogor city’s minimarket (Y). X1, X2, X4, X5, X6 influence partially to the consumer’s buying decisions in Bogor city’s mnimaarket (Y). While X3 has no effect on consumer’s buying decisions in Bogor city’s minimarket (Y). Ambience store become the dominant variables that influence consumer buying decisions in the minimarket at Bogor city.Keywords: Retailing Mix, Buying Decision, Minimarket